Introduction: The Meaning of Modern Architecture - Morgenthaler, Hans Rudolf (The Meaning of Modern Architecture, 2015)
Is Modern architecture-the International Style-just functional design constructed in the most effective manner from the industrial building materials steel, glass, and reinforced concrete? This view is too simplistic. The forms and shapes of Modern art and architecture-from Impressionism to Constructivism in painting and sculpture, and the International Style in architecture-are radically different from those found in earlier periods. They are abstract and devoid of any of the ornamental details that had previously created a sense of familiarity with, and access to, works of art or architecture. Werner Hoffmann once defined Modern painting as that where the artistic creation "took the material substance off of the objective quality" and incorporated this as force lines or "constructive" elements into the pictorial composition. 1 This was a dramatic change because it interrupted the stable foundation of historical and stylistic continuity on which historians and critics had relied for their interpretation. Modernity had established a new foundation that did not provide immediate reference points for orientation. In other words, buildings were no longer representative in the traditional stylistic manner. Like the other Modern forms and media, so architecture also created works and forms that were new both as artistic and real creations in themselves, not recreations or symbolizations of something that already existed.